Reconstruction of Homo Islamicus Concept: Normative Ideals and Reality of Modern Muslim Economic Behaviour - Finita Rahmadani; Sri Dewi Miladiyah; Umamah Mumtazah Askhiyah; Sri Rokhlinasari; Alvien Septian Haerisma (el-Jizya: Jurnal Ekonomi Islam, 2026)
This study aims to reconstruct the concept of Homo Islamicus so that it is not merely a static theological ideal, but rather an adaptive and practical model of economic behaviour capable of addressing the complexities of the modern market. This study employs a qualitative approach using a literature review method to critically analyse the theoretical construct. Data was collected through a literature review of books, academic journals, and relevant academic documents. The data analysis method employed in this study was inductive and contextual, thereby yielding a comprehensive understanding. The findings indicate that the concept of Homo Islamicus is normatively relevant in explaining the economic behaviour of contemporary Muslims in economic decision-making. However, this study indicates a gap in Homo Islamicus between the ideal nature of the concept and the reality of economic practice. In practice, inconsistencies were found between religious values and the economic behaviour of Muslims, which is influenced by environmental and social factors, as well as global market pressures, alongside a lack of internalisation of Islamic economic values. The study’s limitations highlight that Homo Islamicus remains largely normative and philosophical in nature, making it difficult to realise empirically within actual economic practices dominated by conventional systems. There is a gap between the ideal and the reality of actual behaviour, where Muslim individuals are still frequently caught up in materialistic consumption patterns.